Putative Mechanisms for Initial Reaction of Anaerobic Benzene Degradation Presumably Involving a Flavoprotein - Florin Musat; Lars Wöhlbrand; Rene Jarling; Michael Kube; Niculina Musat; Patrick Becker; Stefan Bruns; Richard Reinhardt; Rudolf Amann; Friedrich Widdel; Heinz Wilkes; Ralf Rabus (Environmental Microbiology, 2026)
Biodegradation of benzene is most challenging among the plethora of hydrocarbons due to its high chemical stability. While aerobic bacteria employ O 2 ‐dependent oxygenases to overcome the high energy barrier, anaerobic benzene degradation remains enigmatic. Here we achieve an anaerobic enrichment, which is clonal with respect to the benzene‐degrading, sulphate‐reducing, marine bacterium BzS1, from a previously reported enrichment culture. We investigate this clonal enrichment culture by metabolite and proteogenomic analyses. BzS1 has a tailor‐made catabolic network for utilising benzene, toluene, and acetate. Concerning the initial reaction of anaerobic benzene degradation, labelling experiments render previously suggested direct carboxylation (to benzoate) or methylation (to toluene) unlikely. Accordingly, a benzoate‐CoA ligase is not encoded in the genome and proteins of anaerobic toluene degradation are not detectable in benzene‐utilising cells. Rather, detection of labelled 3‐phenylpropanoate hints at addition of benzene to a C 3 ‐cosubstrate. Moreover, a presumptively heterotrimeric flavoprotein is present at remarkably high abundance (~⅕ of covered proteome) during anaerobic growth with benzene. This protein is related to glycolate oxidase and flavoproteins of the VOA/PCMH family. Taken together, these findings open the possibility of considering flavin cofactor involvement for the initial reaction using, for example, enolpyruvate (central metabolite) or glutaconyl‐CoA (intermediate of benzoyl‐CoA pathway) as cosubstrate.

Generation of Fibrin-Based Aortic Vessels with Layer-Specific Cell Architecture Under Pulsatile Perfusion in a Clinical Organ Care System - Celina Delia Käding; Clara-Sophie Glomb; Patrick Stadler; Imke Becker; Melanie Klingenberg; Hans-Klaus Höffler; Michael Pflaum; Arjang Ruhparwar; Mathias Wilhelmi; Florian Helms (Annals of Biomedical Engineering, 2026)
Purpose Overcoming the limitations of synthetic vascular grafts in the development of biocompatible and regenerative vessels remains a long-term objective in tissue engineering. In this study, we engineered large-diameter fibrin-based vascular grafts with a target inner diameter of 21 mm replicating all three layers of the native human vessel wall in vitro. Methods The Tunica media was reconstructed using a compressed high-density (25 mg/mL) fibrin matrix seeded with smooth muscle cells expressing α-SMA and calponin, differentiated from adipose-derived mesenchymal stem cells (ASCs). The Adventitia -equivalent was formed in a 5 mg/mL fibrin gel containing ASCs, human umbilical vein endothelial cells (HUVECs), and normal human dermal fibroblasts (NHDFs) to enable the formation of a capillary-like network resembling the native adventitial Vasa vasorum . The luminal surface was endothelialized with HUVECs to replicate the Tunica intima . While controls were cultured statically for 7 days, other grafts were evaluated under pulsatile perfusion at physiological pressures using the TransMedics ® “Organ Care System Heart ™ ”. Results The stepwise fabrication technique resulted in three-layered bioartificial vessel equivalents with a mean inner diameter of 21 mm. All constructed vessels ( n = 3) maintained sufficient biomechanical stability to withstand physiological pressure (120.9 ± 1.2 to 61.4 ± 12.5 mmHg) at 60 bpm throughout the perfusion period. The aortic grafts exhibited a cyclic stretch (8.95 ± 2.03%) within the physiological range of native vessels. Mechanical stimulation induced a layer-specific physiological cell morphology and alignment across all three layers of the vascular wall. Endothelial coverage was high on static grafts (81.39 ± 2.37%) and on one of three dynamic grafts. Shear stress during perfusion (0.38 ± 0.03 dyn cm −2 ) remained below physiological levels, and further evaluation under prolonged perfusion (> 21 days) is required to assess long-term biomechanical stability and vascular functionality. Conclusion This approach may be considered a proof of concept and constitutes a first step toward the development of biometric and functional large-diameter vessel replacements.

Topical oleic acid reduces nociception and inflammation in a UVB radiation-induced sunburn model in mice - Patrick Tuzi Serafini; Evelyne Silva Brum; Gabriela Becker; Amanda Favarin; Indiara Brusco; Sara Marchesan Oliveira (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A Soil–Plant–Atmosphere Continuum model coupled to CFD to simulate plant energy and water exchanges in heterogeneous microclimates - Joseph Vernier; Sylvain Edouard; Baptiste Amiot; Martin Ferrand; Andrée Tuzet; Eric Dupont; Céline Caruyer; Mike Van Iseghem; Axel Becker; Didier Combes; Patrick Massin (Agricultural and Forest Meteorology, 2026)

Development, growth, and flower production of cut sunflower under tropical, subtropical, and temperate environments - Regina Tomiozzo; Lilian Osmari Uhlmann; Leosane Cristina Bosco; Márkilla Zunete Beckmann-Cavalcante; Petterson Baptista da Luz; José Carlos Sorgato; Simone Novaes Reis; Lívia Mendes de Carvalho; Anelise Tessari Perboni; Luana Moraes da Luz; Heberte Fernandes de Figueredo; Sebastião Marcos Silva Valentim; et al. (Horticulture, Environment, and Biotechnology, 2025)

Topical diosmetin attenuates nociception and inflammation in a ultraviolet B radiation-induced sunburn model in mice - Amanda Favarin; Gabriela Becker; Evelyne Silva Brum; Patrick Tuzi Serafini; Lara Panazzolo Marquezin; Indiara Brusco; Sara Marchesan Oliveira (Inflammopharmacology, 2024)

Nature 4.0: A networked sensor system for integrated biodiversity monitoring - Dirk Zeuss; Lisa Bald; Jannis Gottwald; Marcel Becker; Hicham Bellafkir; Jörg Bendix; Phillip Bengel; Larissa T. Beumer; Roland Brandl; Martin Brändle; Stephan Dahlke; Nina Farwig; et al. (Global Change Biology, 2024)
Ecosystem functions and services are severely threatened by unprecedented global loss in biodiversity. To counteract these trends, it is essential to develop systems to monitor changes in biodiversity for planning, evaluating, and implementing conservation and mitigation actions. However, the implementation of monitoring systems suffers from a trade‐off between grain (i.e., the level of detail), extent (i.e., the number of study sites), and temporal repetition. Here, we present an applied and realized networked sensor system for integrated biodiversity monitoring in the Nature 4.0 project as a solution to these challenges, which considers plants and animals not only as targets of investigation, but also as parts of the modular sensor network by carrying sensors. Our networked sensor system consists of three main closely interlinked components with a modular structure: sensors, data transmission, and data storage, which are integrated into pipelines for automated biodiversity monitoring. We present our own real‐world examples of applications, share our experiences in operating them, and provide our collected open data. Our flexible, low‐cost, and open‐source solutions can be applied for monitoring individual and multiple terrestrial plants and animals as well as their interactions. Ultimately, our system can also be applied to area‐wide ecosystem mapping tasks, thereby providing an exemplary cost‐efficient and powerful solution for biodiversity monitoring. Building upon our experiences in the Nature 4.0 project, we identified ten key challenges that need to be addressed to better understand and counteract the ongoing loss of biodiversity using networked sensor systems. To tackle these challenges, interdisciplinary collaboration, additional research, and practical solutions are necessary to enhance the capability and applicability of networked sensor systems for researchers and practitioners, ultimately further helping to ensure the sustainable management of ecosystems and the provision of ecosystem services.

How Do Prostomial Sensory Organs Affect Brain Anatomy? Phylogenetic Implications in Eunicida (Annelida) - Sabrina Kuhl; Thomas Bartolomaeus; Patrick Beckers (Journal of Marine Science and Engineering, 2022)
Eunicida is a taxon of marine annelids currently comprising the taxa Eunicidae, Onuphidae, Dorvilleidae, Oenonidae, Lumbrineridae, Histriobdellidae and Hartmaniella. Most representatives are highly mobile hunters sharing the presence of a sophisticated nervous system but differ in the number and shape of prostomial sensory organs (0–3 antennae; 0 or 2 palps; 0, 2 or 4 (+2) buccal lips; 0, 2 or 4 eyes; single-grooved or paired nuchal organs). This makes Eunicida an ideal model to study the following questions: Is the brain morphology affected by different specificities of prostomial sensory organs? Do similar numbers and shapes of prostomial sensory organs hint at close phylogenetic relationships among different eunicidan taxa? How can antennae, palps and buccal lips be differentiated? For the investigation of sensory organs and the nervous system, we performed immunohistochemistry, µCT, TEM, SEM, paraffin histology and semi-thin sectioning. Our results show that brain anatomy is mostly affected on a microanatomical level by sensory organs and that similar specificities of sensory organs support the latest phylogenetic relationships of Eunicida. Further, a reduction of antennae in Eunicida can be suggested and hypotheses about the presence of sensory organs in the stem species of Eunicida are made.

Loss of complexity from larval towards adult nervous systems in Chaetopteridae (Chaetopteriformia, Annelida) unveils evolutionary patterns in Annelida - Conrad Helm; Gudrun Schwarze; Patrick Beckers (Organisms Diversity & Evolution, 2022)
Chaetopteridae — the parchment worms — comprise a group of early branching annelids with a scarcely investigated neuroanatomy and neurogenesis. Due to their phylogenetic position in the annelid tree, studying them is nevertheless inevitable for our understanding of character evolution in segmented worms. Therefore, we investigated several adult und larval chaetopterids using a broad set of morphological methods — including serial azan-stained histological sections as well as ultrastructural and immunohistochemical approaches. Our investigations shows that the chaetopterid nervous system consists of a medullary and intraepidermal anterior brain without major commissures and only one neuron type. Nuchal organs and complex cup-shaped eyes are absent in adult specimens. The developmental investigations reveal an antero-posterior origin of the larval nervous system, which is in line with previous investigations and supports this character as being plesiomorphic at least for Annelida. Furthermore, the reduction of neuronal complexity during ontogenesis hints towards the necessity of developmental examinations to understand the evolutionary scenarios behind nervous system diversity not only in annelid taxa. Our detailed investigations will help to deepen our knowledge in terms of annelid character evolution and will build up a basis for further detailed examinations dealing with this fascinating group of segmented worms.

Complex and flexible catabolism in Aromatoleum aromaticum pCyN1 - Patrick Becker; Annemieke Döhmann; Lars Wöhlbrand; Daniela Thies; Christina Hinrichs; Ramona Buschen; Daniel Wünsch; Meina Neumann‐Schaal; Dietmar Schomburg; Michael Winklhofer; Richard Reinhardt; Ralf Rabus (Environmental Microbiology, 2022)
Summary Large quantities of organic matter are continuously deposited, and (a)biotic gradients intersect in the soil–rhizosphere, where biodegradation contributes to the global cycles of elements. The betaproteobacterial genus Aromatoleum comprises cosmopolitan, facultative denitrifying degradation specialists. Aromatoleum aromaticum . pCyN1 stands out for anaerobically decomposing plant‐derived monoterpenes in addition to monoaromatic hydrocarbons, polar aromatics and aliphatics. The catabolic network's structure and flexibility in A . aromaticum pCyN1 were studied across 34 growth conditions by superimposing proteome profiles onto the manually annotated 4.37 Mbp genome. Strain pCyN1 employs three fundamentally different enzymes for C–H‐bond cleavage at the methyl groups of p ‐cymene/4‐ethyltoluene, toluene and p ‐cresol respectively. Regulation of degradation modules displayed substrate specificities ranging from narrow (toluene and cyclohexane carboxylate) via medium‐wide (one module shared by p ‐cymene, 4‐ethyltoluene, α‐phellandrene, α‐terpinene, γ‐terpinene and limonene) to broad (central benzoyl‐CoA pathway serving 16 aromatic substrates). Remarkably, three variants of ATP‐dependent (class I) benzoyl‐CoA reductase and four different β‐oxidation routes establish a degradation hub that accommodates the substrate diversity. The respiratory system displayed several conspicuous profiles, e.g. the presence of nitrous oxide reductase under oxic and of low‐affinity oxidase under anoxic conditions. Overall, nutritional versatility in conjunction with network regulation endow A . aromaticum pCyN1 with broad adaptability.

Flashback phenomena after administration of LSD and psilocybin in controlled studies with healthy participants - Felix Müller; Elias Kraus; Friederike Holze; Anna Becker; Laura Ley; Yasmin Schmid; Patrick Vizeli; Matthias E. Liechti; Stefan Borgwardt (Psychopharmacology, 2022)
Background LSD and psilocybin are increasingly used in phase I trials and evaluated as therapeutic agents for mental disorders. The phenomenon of reoccurring drug-like experiences after the acute substance effects have worn off was described for both substances and especially attributed to LSD. According to the DSM-V, the persisting and distressing manifestation of these experiences is called hallucinogen-persisting perception disorder (HPPD). Data on both conditions is very limited. Objective This study aims to provide descriptive data on reoccurring drug-like experiences after the administration of LSD and psilocybin in controlled studies with healthy participants. Methods and materials Data from 142 healthy subjects enrolled in six double-blinded, placebo-controlled, randomized cross-over studies were analyzed. In total, 60 subjects received LSD; 27 subjects received LSD, MDMA, and d -amphetamine; 31 subjects received LSD and psilocybin; and 25 subjects received psilocybin and escitalopram. At the end-of-study visit (mean 39.8 days after last study session, SD 37.2), subjects were asked for any reoccurring drug effects since the initial substance effects had worn off. Those reporting reoccurring perception changes more than 24 h after administration were contacted for follow-up (mean follow-up duration: 31.2 months, SD 28.6). Results Thirteen out of 142 subjects reported reoccurring drug-like experiences (LSD: seven, psilocybin: two, both: four). The reported phenomena were predominantly mild and perceived as neutral to pleasant. Flashbacks were mostly of visual nature, lasted for seconds to minutes, and occurred within a week after the last drug administration. Two subjects reported distressing experiences that subsided spontaneously. One subject reported brief and pleasant visual perception changes which reoccurred for 7 months. None of the subjects reported impairment in their daily lives. None of the cases met DSM-V criteria for HPPD. Conclusion Reoccurring drug-like experiences after the administration of LSD and psilocybin are a common phenomenon occurring in up to 9.2% of healthy subjects (7.8% for LSD, 8.3% for psilocybin and 14.3% if both substances are administered). Additionally, our work suggests that flashback phenomena are not a clinically relevant problem in controlled studies with healthy participants.

Correction to: Fine structure of mushroom bodies and the brain in Sthenelais boa (Phyllodocida, Annelida) - Patrick Beckers; Carla Pein; Thomas Bartolomaeus (Zoomorphology, 2022)
Unfortunately, the captions of figures were incorrectly published in original publication. The corrected version updated here.

Fine structure of mushroom bodies and the brain in Sthenelais boa (Phyllodocida, Annelida) - Patrick Beckers; Carla Pein; Thomas Bartolomaeus (Zoomorphology, 2022)
Mushroom bodies are known from annelids and arthropods and were formerly assumed to argue for a close relationship of these two taxa. Since molecular phylogenies univocally show that both taxa belong to two different clades in the bilaterian tree, similarity must either result from convergent evolution or from transformation of an ancestral mushroom body. Any morphological differences in the ultrastructure and composition of mushroom bodies could thus indicate convergent evolution that results from similar functional constraints. We here study the ultrastructure of the mushroom bodies, the glomerular neuropil, glia-cells and the general anatomy of the nervous system in Sthenelais boa . The neuropil of the mushroom bodies is composed of densely packed, small diameter neurites that lack individual or clusterwise glia enwrapping. Neurites of other regions of the brain are much more prominent, are enwrapped by glia-cell processes and thus can be discriminated from the neuropil of the mushroom bodies. The same applies to the respective neuronal somata. The glomerular neuropil of insects and annelids is a region of higher synaptic activity that result in a spheroid appearance of these structures. However, while these structures are sharply delimited from the surrounding neuropil of the brain by glia enwrapping in insects, this is not the case in Sthenelais boa . Although superficially similar, there are anatomical differences in the arrangement of glia-cells in the mushroom bodies and the glomerular neuropil between insects and annelids. Hence, we suppose that the observed differences rather evolved convergently to solve similar functional constrains than by transforming an ancestral mushroom body design.

The Seasonal and Inter-Annual Fluctuations of Plankton Abundance and Community Structure in a North Atlantic Marine Protected Area - Fabio Benedetti; Laëtitia Jalabert; Marc Sourisseau; Beatriz Becker; Caroline Cailliau; Corinne Desnos; Amanda Elineau; Jean-Olivier Irisson; Fabien Lombard; Marc Picheral; Lars Stemmann; Patrick Pouline (Frontiers in Marine Science, 2019)

Nemertean taxonomy—Implementing changes in the higher ranks, dismissing Anopla and Enopla - Malin Strand; Jon Norenburg; José E. Alfaya; Fernando Ángel Fernández‐Álvarez; Håkan S Andersson; Sonia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Gregorio Bigatti; Irina Cherneva; Alexey Chernyshev; Brian M. Chung; et al. (Zoologica Scripta, 2019)

The nervous systems of Hoplonemertea (Nemertea) - Patrick Beckers; Daria Krämer; Thomas Bartolomaeus (Zoomorphology, 2018)

Genus richness of microalgae and Cyanobacteria in biological soil crusts from Svalbard and Livingston Island: morphological versus molecular approaches - Martin Rippin; Nadine Borchhardt; Laura Williams; Claudia Colesie; Patrick Jung; Burkhard Büdel; Ulf Karsten; Burkhard Becker (Polar Biology, 2018)

The Chan Hol cave near Tulum (Quintana Roo, Mexico): evidence for long‐lasting human presence during the early to middle Holocene - Fabio Hering; Wolfgang Stinnesbeck; Jens Folmeister; Eberhard Frey; Sarah Stinnesbeck; Jerónimo Avilés; Eugenio Aceves Núñez; Arturo González; Alejandro Terrazas Mata; Martha Elena Benavente; Carmen Rojas; Adriana Velázquez Morlet; et al. (Journal of Quaternary Science, 2018)
Numerous charcoal accumulations discovered in the submerged Chan Hol cave near Tulum, Quintana Roo, Mexico, have been 14 C‐dated revealing ages between 8110 ± 28 14 C a BP (9122–8999 cal a BP) and 7177 ± 27 14 C a BP (8027–7951 cal a BP). These charcoal concentrations, interpreted here as ancient illumination sites, provide strong evidence that the Chan Hol cave was dry and accessible during that time interval. Humans used the cave for at least 1200 years during the early and middle Holocene, before access was successively interrupted by global sea level rise and flooding of the cave system. Our data thus narrow the gap between an early settlement in the Tulum area reaching from the late Pleistocene (∼13 000 a) to middle Holocene (e.g. 7177 14 C a BP), and the Maya Formative period at approximately 3000 a bp. Yet, no evidence has been presented to date for human settlement during the ∼4000‐year interval between 7000 and 3000 a. This is remarkable as settlement in other areas of south‐eastern Mexico (e.g. Chiapas, Tabasco) and in Guatemala was apparently continuous.

Unravelling the Lineus ruber/viridis species complex (Nemertea, Heteronemertea) - Daria Krämer; Christian Schmidt; Lars Podsiadlowski; Patrick Beckers; Lisa Horn; Jörn von Döhren (Zoologica Scripta, 2017)
Lineus ruber (Müller, ) and Lineus viridis (Müller, ) are among the longest known and most abundant intertidal nemertean species found on both sides of the North Atlantic. Due to easy maintenance in captivity, both species have been well studied concerning morphology, reproduction, development and ecology. Originally described as two separate species in the 18th century, they were subsequently synonymised and considered colour varieties of a single species. It was not until the mid‐20th century that complementary redescriptions, including information on reproduction and development, re‐established the specific identities of L. ruber and L. viridis . With the advent of molecular markers in nemertean systematics, however, doubt was again cast on their specific identities. To solve one of the longest standing problems in nemertean systematics, we assembled a comprehensive data set combining external morphology and three genetic markers (mitochondrial cytochrome c oxidase subunit I, 16S rRNA and nuclear internal transcribed spacer region) from 160 specimens of L. ruber and L. viridis collected at six sampling sites along the continental coast of Western Europe. The data set was analysed with tree‐based and non‐tree‐based species delimitation methods. The results from all methods used confidently delimit three separate clades. A distinct barcoding gap was detected in our data set which thus provides a framework to unequivocally identify specimens as members of any of the three species. Comparison of our findings with published data enables us to assign one lineage to L. ruber and one to L. viridis . We designated neotypes for both species. The third clade is very similar to L. viridis , only distinguishable by a conspicuous, iridescent ventral fold in some male specimens This lineage shows a syntopic distribution along western European coasts and represents a species new to science and is described as Lineus clandestinus sp. n. based on its external characters and the analyses of the molecular data provided in this study.

The future of nemertean taxonomy (phylum Nemertea) — a proposal - Per Sundberg; Sónia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Jörn von Döhren; Daria Krämer; Ray Gibson; Gonzalo Giribet; Alfonso Herrera‐Bachiller; Juan Junoy; Hiroshi Kajihara; Sebastian Kvist; et al. (Zoologica Scripta, 2016)

Root traits contributing to drought tolerance of synthetic hexaploid wheat in a greenhouse study - Steven R. Becker; Patrick F. Byrne; Scott D. Reid; William L. Bauerle; John K. McKay; Scott D. Haley (Euphytica, 2016)

Phylogenetic significance of chaetal arrangement and chaetogenesis in Maldanidae (Annelida) - Ekin Tilic; Jörn von Döhren; Björn Quast; Patrick Beckers; Thomas Bartolomaeus (Zoomorphology, 2015)

Low-dose photon irradiation alters cell differentiation via activation of hIK channels - Bastian Roth; Christine S. Gibhardt; Patrick Becker; Manuela Gebhardt; Jan Knoop; Claudia Fournier; Anna Moroni; Gerhard Thiel (Pflügers Archiv - European Journal of Physiology, 2015)

The nervous systems of Pilidiophora (Nemertea) - Patrick Beckers (Zoomorphology, 2015)

Functional characterization of zebrafish K2P18.1 (TRESK) two-pore-domain K+ channels - Ann-Kathrin Rahm; Felix Wiedmann; Jakob Gierten; Constanze Schmidt; Patrick A. Schweizer; Rüdiger Becker; Hugo A. Katus; Dierk Thomas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

The metallohormone cadmium modulates AhR-associated gene expression in the small intestine of rats similar to ethinyl-estradiol - Felix M. Kluxen; Patrick Diel; Nicola Höfer; Eugenia Becker; Gisela H. Degen (Archives of Toxicology, 2013)

Novel electrophysiological properties of dronedarone: inhibition of human cardiac two-pore-domain potassium (K2P) channels - Constanze Schmidt; Felix Wiedmann; Patrick A. Schweizer; Rüdiger Becker; Hugo A. Katus; Dierk Thomas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Mesenchymal stromal cells (MSCs): science and f(r)iction - Karen Bieback; Patrick Wuchter; Daniel Besser; Werner Franke; Matthias Becker; Michael Ott; Martin Pacher; Nan Ma; Christof Stamm; Harald Klüter; Albrecht Müller; Anthony D. Ho (Journal of Molecular Medicine, 2012)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)